Adenine as a Halogen Bond Acceptor: A Combined Experimental and DFT Study - Yannick Roselló; Mónica Benito; Elies Molins; Miquel Barceló-Oliver; Antonio Frontera (Crystals, 2019)
In this work, we report the cocrystallization of N9-ethyladenine with 1,2,4,5-tetrafluoro-3,6-diiodobenzene (TFDIB), a classical XB donor. As far as our knowledge extends, this is the first cocrystal reported to date where an adenine derivative acts as a halogen bond acceptor. In the solid state, each adenine ring forms two centrosymmetric H-bonded dimers: one using N1···HA6−N6 and the other N7···HB6−N6. Therefore, only N3 is available as a halogen bond acceptor that, indeed, establishes an N···I halogen bonding interaction with TFDIB. The H-bonded dimers and halogen bonds have been investigated via DFT (Density Functional Theory) calculations and the Bader’s Quantum Theory of Atoms In Molecules (QTAIM) method at the B3LYP/6-311+G* level of theory. The influence of H-bonding interactions on the lone pair donor ability of N3 has also been analyzed using the molecular electrostatic potential (MEP) surface calculations.